Temporal fluctuations in the sero-prevalence of Taenia solium cysticercosis in pigs in Mbeya Region, Tanzania - Uffe Christian Braae; Pascal Magnussen; Faustin Lekule; Wendy Harrison; Maria Vang Johansen (Parasites & Vectors, 2014)
Abstract Background Porcine cysticercosis is an emerging agricultural problem in sub-Saharan Africa. This has been documented primarily through cross-sectional studies, however detailed knowledge of the transmission dynamics of this disease in sub-Saharan Africa is lacking. This study aims to describe seasonal variations in sero-prevalence of antigen ELISA positive porcine cysticercosis in an endemic area. Methods A longitudinal study composed of three cross-sectional surveys was carried out in Mbeya Region, Tanzania; the first two six months apart (March/April 2012 and October/November 2012) and the last eight months later (July/August 2013). Venous blood was collected from pigs in 22 villages and analysed using Ag-ELISA. Results In each survey between 800–1000 serum samples were collected. The first survey revealed a cysticercosis sero-prevalence of 15% (n = 822, 95% CI: 13-18%). The sero-prevalence had significantly increased to 24% (p < 0.001, χ2-test, n = 812, 95% CI: 21-27%) at the time of the 6 month follow-up. At 14-months the sero-prevalence had dropped to 20% (p = 0.053, χ2-test, n = 998, 95% CI: 18-23%). Overall, this was a reduction in sero-prevalence compared with a study conducted in 2007 in the same area, where 31% (186/600) of pigs were found positive. Conclusion Confined pigs did not have a lower sero-prevalence compared to free roaming pigs in any of the three surveys. Several factors may have contributed to the observed fluctuations such as African swine fever or seasonal variation in local crop production practices. Also, as the Ag-ELISA assay used is not species specific, variation in transmission of Taenia hydatigena could potentially influence the results. The observed fluctuations contradict a theoretical model which predicts a stable equilibrium, which only considers a two-compartment (pig and human) model excluding the effect of the environment. Whether the disease has an endemic equilibrium, or undergoes fluctuations dependent on extrinsic and/or socio-economic factors remains to be elucidated.